PENGARUH PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN DAN DAMPAKNYA TERHADAP LOYALITAS PELANGGAN PADA RESTAURANT NESTCOLOGY SEMARANG - Dina Erlyana, 13.05.51.0010; Waru wu, Penunjang (Students' Journal of Economic and Management, 2018)
Restaurant Nestcology Semarang brings the concept as a fine dining restaurant, Resturant Nestcology Semarang is intended to provide a new experience for foodies in Semarang, do not be surprised if the restaurant is also taking the tagline as the Land of Gastronomy. The problem is based on the study data as disclosed by Santos Thenu, that for a non-franchise of 100 stores, closed 80, so his survival 20%, franchise are more likely tosurvive, even for those who want to buy a franchise must exit costs more expensive. Where 80 cap was nearly half over because the wrong places. It is a challenge for resturant Nestcology to exist and survive.The purpose of this study was to analyze the influence between service and product quality to customer satisfaction, to analyze the influence of Customer Satisfaction to Customer Loyalty, and to analyze the impact of service and product quality on Customer Loyalty with Customer Satisfaction Mediated by at Restaurant Nestcology Semarang. The population in this study are customers of the visitors restaurant Nestcology Semarang, whosenumber fluktutatif (not necessarily), taken as many as 96 respondents in the sample (Ridwan and Akdon, 2013), using incidental sampling technique, further analyzed using multiple regression. The conclusion of this study is that the variable service and product quality has a positive influence and significant impact on customer satisfaction, and variable customer satisfaction has a positive influence and significant impact on customer loyalty, customer satisfaction is not statistically proven to mediate the effect of service on customer loyalty, but customer satisfaction statistically proven to mediate the effect of product quality to customer loyalty.Keywords : Service, Quality Products, Restaurant Nestcology